Application of The SiMaYang Type II Learning Model in Increasing Understanding of The Concept of Chemical Bonds - Agustina, Ni Putu Rahma (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
SiMaYang (Si Lima Layang-Layang) Learning Model is an approach designed to combine aspects of simulation and real analogies in the learning process. This model aims to increase student involvement, make it easier to understand the material, and encourage critical thinking skills Purpose: The aim of this research is to analyze the effectiveness of the SiMaYang learning model in improving students' conceptual understanding of chemical bonding material. Method: The research employed a quasi-experimental method with a pretest-posttest control group design. Findings: A comparative analysis between the experimental class, which implemented the SiMaYang model, and the control class, which utilized a conventional approach, revealed substantial differences in learning outcomes. At the outset, both groups demonstrated similar baseline abilities, with pretest scores showing only 28% correct answers. Following the application of the SiMaYang model, the experimental class exhibited a remarkable improvement, achieving 93.3% correct answers in the posttest. In contrast, the control class only reached 59.1% correct answers with N-gain values between the control class (0.43) and the experimental class (0.94) This significant disparity underscores the effectiveness of the SiMaYang model in enabling students to construct knowledge more effectively. Conclusion: The SiMaYang learning model has been demonstrated to significantly enhance the quality of chemistry education. From a methodological perspective, the SiMaYang model successfully develops students' metacognitive skills through a structured approach that actively engages them in constructing knowledge, engaging in critical reflection, and formulating their own thinking strategies.Keywords: SiMaYang Type II, Learning Model, Chemical Bond.DOI: 10.23960/jppk.v13.i3.32853